True intraindividual change models: An exampe of stress appraisals and coping - Buško, Vesna (Array, 2005)
The study examines intraindividual variations in self-report measures of coping with low-control stress by means of the true change modeling procedures. Within the particular class of structural equation models, as put forward by Steyer et al. (1997, 2000), the true intraindividual change scores between two occasions of measurement correspond to the values of endogenous latent variables. Such a specification further enables examining correlates and predictors of true change between the measurements. Transactional stress and coping theory views the processes of coping as context-specific and varying across time and the attributes of concrete stressful situations. Yet, substantial interindividual differences in the change scores can still be found in the measures of coping with any kind of situational demands. The data on cognitive appraisals and three broad situation-specific coping measures were collected on two occasions on the sample of 421 military basic trainees. The tested structural equation models and the parameters obtained point to different patterns of relationships of latent state and latent change coping measures with particular antecedent and appraisal variables.